Madrasas and NGOs : Complements or Substitutes? Non-State Providers and Growth in Female Education in Bangladesh - Asadullah, Mohammad Niaz; Chaudhury, Nazmul (World Bank, Washington, DC, 2012)
There has been a proliferation of non-state providers of education services in the developing world. In Bangladesh, for instance, Bangladesh Rural Advancement Committee runs more than 40,000 non-formal schools that cater to school-drop outs from poor families or operate in villages where there's little provision for formal schools. This paper presents a rationale for supporting these schools on the basis of their spillover effects on female enrollment in secondary (registered) madrasa schools (Islamic faith schools). Most madrasa high schools in Bangladesh are financed by the sate and include a modern curriculum alongside traditional religious subjects. Using an establishment-level dataset on student enrollment in secondary schools and madrasas, the authors demonstrate that the presence of madrasas is positively associated with secondary female enrollment growth. Such feminization of madrasas is therefore unique and merits careful analysis. The authors test the effects of the Bangladesh Rural Advancement Committee primary schools on growth in female enrollment in madrasas. The analysis deals with potential endoegeneity by using data on number of the number of school branches and female members in the sub-district. The findings show that madrasas that are located in regions with a greater number of Bangladesh Rural Advancement Committee schools have higher growth in female enrollment. This relationship is further strengthened by the finding that there is, however, no effect of these schools on female enrollment growth in secular schools.